Ultrasonic pre-treatment of sludge for anaerobic digestion - Show, Kuan Yeow (2011)
Large quantities of sludge are produced in the treatment of municipal wastewater. The sludge is highly putrescible and must be stabilized for safe disposal or applications. Anaerobic digestion is the most popular process for stabilization of wastewater sludge. Along with mass reduction, odor and pathogen removal, an attractive feature of anaerobic digestion is its ability to accomplish energy recovery in the form of biogas leading to a cost-effective operation. However, as anaerobic degradation of sludge is a complex and sensitive biological process, maintaining a satisfactory and consistent digester performance can be a challenging task. In dealing with sludge containing recalcitrant and complex substances, a much longer degradation process is essential to accommodate the ratelimiting hydrolysis of complex organics to simpler metabolites. To maintain satisfactory degradation, large-size digesters are normally required. Studies have been explored into the use of pretreatment in accelerating and enhancing anaerobic degradation. Amongst many pretreatment methods employed, ultrasound sonication exhibits a lower extent of impact to the environment and greater cost competitiveness.